PROFIL KONSEP DIRI NEGATIF PADA PESERTA DIDIK BROKEN HOME KELAS XI DI SMAN RANCAKALONG - Niar Yusmaniar; R. Ika Mustika; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This study aims to describe the negative self-concept of students who have experienced a broken home. Broken home families have the opportunity to make children have a negative self-concept. This is because in a broken home there is a conflict so that the family is not harmonious. This research was conducted using qualitative research. The data collected in this study are data obtained by means of interviews, observation and documentation study. There were 3 subjects in this study, namely HS, DK and AA. The results showed that students who have a broken home family background have a negative self-concept. They have low self-esteem so that behaviors that appear are inappropriate / deviant behavior such as frequent truancy, smoking in the school environment, violating school rules, always being late at school, disobeying the teacher, not doing tasks that are wrong. given. Thus social interactions and social relationships are disrupted and result in obstruction of efforts to develop themselves. In addition, there are also feelings of inferiority, low self-esteem, feeling unnoticed, unlucky and different from other people.Keywords: Negative Self-Concept, Broken Home, Students